Amoxicillin plus omeprazole versus triple therapy for eradication of Helicobacter pylori in duodenal ulcer disease: a prospective, randomized, and controlled study. Issue 9 (September 1993) - Labenz, J; Gyenes, E; Rühl, G H; Börsch, G
Abstract : Treatment with amoxicillin and omeprazole resulted in encouraging Helicobacter pylori eradication rates in pilot studies that included medium term follow up. These results were evaluated in a prospective, randomised and controlled study. Forty patients with active duodenal ulcer disease and H pylori colonisation of the gastric mucosa were randomly assigned to receive either omeprazole (20 mg twice daily) and amoxicillin suspension (500 mg four times daily) for two weeks (group I) or bismuth subsalicylate (600 mg three times daily), metronidazole (400 mg three times daily), tetracycline (500 mg three times daily), and ranitidine (300 mg in the evening) for two weeks (group II). Study medication was followed in both groups by a four week treatment course with 300 mg ranitidine up to the final examination. One patient from each group was lost to follow up. H pylori was eradicated in 78.9% of group I and 84.2% of group II (p = 1.00). All ulcers in patients on omeprazole plus amoxicillin healed but in the triple treatment group four patients had residual peptic lesions after six weeks (ulcer healing rate: 78.9%, p = 0.11). Complete pain relief occurred after a median duration of 1 day in group I and of 6 days in group II (p = 0.03). There were no major complications in either group but minor side effects were more frequently recorded in patients on triple therapy (63.2% v 15.8%, p < 0.01). In conclusion, two weeks of treatment with omeprazole plus amoxicillin is as good as triple therapy plus ranitidine in eradicating H pylori but seems better with regard to safety, pain relief, and ulcer healing. Thus, amoxicillin plus omeprazole should be recommended as the treatment of choice in eradicating H pylori in patients with duodenal ulcer disease.